2021
DOI: 10.3389/fnins.2021.705890
|View full text |Cite
|
Sign up to set email alerts
|

DRD1 and DRD2 Receptor Polymorphisms: Genetic Neuromodulation of the Dopaminergic System as a Risk Factor for ASD, ADHD and ASD/ADHD Overlap

Abstract: The dopaminergic system (DS) is one of the most important neuromodulator systems involved in complex functions that are compromised in both autism spectrum disorder (ASD) and attention deficit/hyperactivity disorder (ADHD), conditions that frequently occur in overlap. This evidence suggests that both disorders might have common neurobiological pathways involving the DS. Therefore, the aim of this study was to examine the DRD1 and DRD2 dopamine receptor single nucleotide polymorphisms (SNPs) as potential risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…DRD2 Taq1A (rs1800497) ( Neville et al, 2004 ; Pan et al, 2015 ) has been reported to relate to DRD2 expression levels ( Laakso et al, 2005 ). DRD2-12 ( rs7131465 ) is related to a higher risk for ADHD and autism spectrum disorder overlap ( Mariggiò et al, 2021 ). The intronic DRD2 SNPs (rs1079727, rs1079595, and rs1124491), and SNP in the 3’-UTR (rs1800497) have been linked with ADHD in males ( Nyman et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…DRD2 Taq1A (rs1800497) ( Neville et al, 2004 ; Pan et al, 2015 ) has been reported to relate to DRD2 expression levels ( Laakso et al, 2005 ). DRD2-12 ( rs7131465 ) is related to a higher risk for ADHD and autism spectrum disorder overlap ( Mariggiò et al, 2021 ). The intronic DRD2 SNPs (rs1079727, rs1079595, and rs1124491), and SNP in the 3’-UTR (rs1800497) have been linked with ADHD in males ( Nyman et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, one may assume that the increase in neurons with D2R in the VTA of Clstn2-KO mice reported herein may be associated with an increased locomo tor activity of these animals. It is also interesting to note that human studies have shown that nucleotide polymorphism in the D2R gene can be considered as a potential risk factor for the development of not only ASD, but also attention deficit hyperactivity disorder (Mariggio et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2) , including the negative regulation of neuron differentiation (GO:0045665, hit 45 in observed failed lines) or the regulation of neuron apoptotic process (GO:0043523, hit 82 in predicted failed lines). The most mutated genes (log 2 FC>1.5) contributing to the enrichment of those biological processes in failed lines are well-known disease associations: NSUN5 in William Beuren Syndrome 21 , FOXG1 in FOXG1-syndrome 22 , DRD1 in Autism Disorder 23 or ASCL1 in neuropsychiatric disorders 24 . In other cases, those genes are key regulators of neuron differentiation like NRBP2 for neural progenitor cell (NPC) survival 25 , DMRTA2 for NPC maintenance 26 , S100A8 involved in microglial inflammation 27 or SOX14, essential for the initiation of neuron differentiation 28 .…”
Section: The Genome-wide Burden Of Acquired Mutations Does Not Explai...mentioning
confidence: 99%